Improved method for detection of glycosidases in bacterial colonies. - Paoni, N F (1984)
An assay has been developed to detect bacterial glycosidases in colonies grown on the surface of agar plates. Advantages of this technique over previously described methods include elimination of the need for replica plating, better visualization of chromagenic reaction products, and a simple permeabilization step to enable better penetration by chromagenic substrates.